Modernising vocational education and training : fourth report on vocational education and training research in Europe: executive summary - (:unkn) unknown (Publications Office of the European Union, 2009)
"Between 2006 and 2008, the European Centre for the Development of Vocational Training (Cedefop) conducted research on the needs and ways of modernising VET in the EU beyond 2010. The resulting papers are the basis of Cedefop's fourth report on VET research. This executive summary reviews the major issues analysed in the report, and the findings and conclusions reached. It outlines the expectations placed on VET by policy-makers, firms, labour markets, VET professionals and users, and society as a whole. The major challenges and future prospects for policy and research are also presented." (Herausgeber, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; G 2 Trends & Entwicklungen; T 1 Forschungsrichtungen; I 2.2 Europa; Berufsbildung; Modernisierung; Reform; Berufsbildungsforschung; Europa